Noget om Myterne omkring den Clausenske injuriesag og Grundtvigs censurperiodes afslutning - Dam, Poul (Grundtvig-studier, 1999)
Historical Aspect; concerning the Civil Liberals against Grundtvig By Poul Dam For eleven years, viz. 1826-1837, Grundtvig had to submit all that he wanted to publish in Denmark to the public censor. A prolific and serious writer like Grundtvig must necessarily have felt this as highly embarrassing, and many of his biographers have painted his ordeal in dark colours, in fact much darker than Grundtvig did himself.Certain facts have indeed been misunderstood to such an extent that even very competent writers have believed and repeated distorted and/or simplified renderings of the actual background.In 1826 Grundtvig published a very harsh attack on a book by the theologian H.N. Clausen, who reacted by bringing a civil libel case against Grundtvig. The court found him guilty of using unseemly language, but not of libelling Clausen, and fined him quite leniently. The probably unforeseen consequence of the sentence, which is quoted in full in the article, was, however, to make Grundtvig subject to lifelong censorship. This was not mentioned at all in the court proceedings, however, since it followed without in all cases when the accused was not acquitted completely. Consequently Grundtvig was not actually sentenced to censorship. The law was modified in 1837 in such a way that Grundtvig could ask to be exempted from censorship, and this happened towards the end of that year.His first book after that to be published without the despicable »imprimatur« of the censor contained a rather long poem about the mother tongue, quite literally defined as the tongue of the mother, of women. A short selection of the verses from this poem has been used as a »national« song praising the Danish language, and this may explain why some writers believe the poem to have been written in a joyful mood directly after the lifting of the censorship. That is an unsubstantiated and more than doubtful construction, however, as nothing in the poem points to a connection with Grundtvig’s actual experiences in 1837.In addition, the article stresses that Grundtvig and Clausen did not remain enemies for life, as many writers have suggested. Both of them came to regard the bitter fight of 1826 as something to regret.